1999
DOI: 10.1111/j.1539-6924.1999.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Fishing in Urban New Jersey: Ethnicity Affects Information Sources, Pe ception, and Compliance

Abstract: Recreational and subsistence angling are important aspects of urban culture for much of North America where people are concentrated near the coasts or major rivers. Yet there are fish and shellfish advisories for many estuaries, rivers, and lakes, and these are not always heeded. This paper examines fishing behavior, sources of information, perceptions, and compliance with fishing advisories as a function of ethnicity for people fishing in the Newark Bay Complex of the New York-New Jersey Harbor. We test the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…3,7,10 Early risk communication research centered on debates about the health or environmental risks associated with waste disposal, toxic chemicals and heavy metals, air and water pollution, nuclear power, electric and magnetic fields, oil spills, food additives, radon in homes, and biotechnology. 2,[11][12][13][14][15][16][17] Little attention was paid to risks caused by exposure to pathogens or to health belief models developed for addressing personal risk-taking behavior (e.g., smoking, alcohol consumption, and drug addiction).…”
mentioning
confidence: 99%
“…3,7,10 Early risk communication research centered on debates about the health or environmental risks associated with waste disposal, toxic chemicals and heavy metals, air and water pollution, nuclear power, electric and magnetic fields, oil spills, food additives, radon in homes, and biotechnology. 2,[11][12][13][14][15][16][17] Little attention was paid to risks caused by exposure to pathogens or to health belief models developed for addressing personal risk-taking behavior (e.g., smoking, alcohol consumption, and drug addiction).…”
mentioning
confidence: 99%
“…If there exists a clear framework and clearly defined policies then it follows that any person or stakeholder is able to see the chain of reporting, clear rule definitions, and identify accountable parties. We provide a case study to show disparity in providing information across a population and the importance of transparent communications [25,26].…”
Section: Compliancementioning
confidence: 99%
“…Understanding the degree to which these populations are exposed and directing risk communication to those most affected is essential to protecting those most at risk (Burger et al 1999;Shilling et al 2010). This study used populations described in the literature that were not specific to the basins being simulated, although it is assumed that some of the fishers in the modeled basins would have characteristics similar to the literature derived populations.…”
Section: Fish Intake and Consumption Advisoriesmentioning
confidence: 99%
“…In addition to enhanced sensitivity, some populations are more susceptible because exposure is greater. Studies of fish consumption by ethnic and other subgroups have consistently found that certain populations consume substantially greater amounts of fish than the general population (Burger et al 1999;Shilling et al 2010;Lincoln et al 2011). Executive Order 12898 (1994 mandates that federal agencies make environmental justice a part of their mission and address human health and environmental effects on minority and low income populations.…”
Section: Introductionmentioning
confidence: 99%